Műszaki-technikai kultúra és oktatás - Lükő, István (Kultúratudományi Szemle, 2022)
Technical culture and education István Lükő There are hundreds of scientifically demanding formulations on the concept of culture, rooted in colere, to cultivate. The term has been applied primarily to the cultivation of the earth. The development of technical culture has become a decisively important sub-area in the use of the term culture and in social practice. In this study we present the conceptual network and elements of culture (activity, experience, system of norms), the modern interpretation of technical-technical culture, information culture, technical-technology within an interdisciplinary framework. The focus is on the factors, effects and educational-training aspects of technical development. We cover the most important aspects of engineering education and vocational training along the aspects of the history of science and the history of education.